IAQ guidelines for selected volatile organic compounds (VOCs) in the UK. (November 2019) - Shrubsole, C.; Dimitroulopoulou, S.; Foxall, K.; Gadeberg, B.; Doutsi, A.
Abstract: Poor indoor air quality, can cause a variety of adverse health effects. Pollutant exposure levels inside buildings are likely due to pollutants from both indoor and outdoor sources. Although there are many indoor airborne pollutants, the current review focusses on Volatile Organic Compounds (VOCs), and considers the current Total Volatile Organic Compounds (TVOC) standards alongside other guideline values, to control levels within the indoor environment. We reviewed the current scientific data showing the occurrence of various VOCs in buildings internationally, and the available toxicological reviews for the individual VOCs with potential for adverse health effects that require attention. We considered available health-based general population indoor guidelines for long and short-term exposure in respect of individual compounds, including acetaldehyde, α-pinene, d -limonene, formaldehyde, naphthalene, styrene, tetrachloroethylene, toluene and xylenes (mixture). We conclude individual VOC guidelines are the most appropriate way forward and that TVOC can be used as an indicator for indoor air quality. This study highlights which compounds should be prioritised for monitoring purposes. Our findings inform discussions around the improvement of general population health, source control and the need to raise awareness of the potential impacts of pollutants in the home.